On Laplacian Equienergetic Signed Graphs - Qingyun Tao; Lixin Tao (Journal of Mathematics)
The Laplacian energy of a signed graph is defined as the sum of the distance of its Laplacian eigenvalues from its average degree. Two signed graphs of the same order are said to be Laplacian equienergetic if their Laplacian energies are equal. In this paper, we present several infinite families of Laplacian equienergetic signed graphs.